Procedure For Determining The Receipt Of Life Insurance Benefits - Sofyan Mei Utama; Endang Pujiastuti; Isni Rubiantini; Mas Putra Zeno Januarsyah; Asep Suryadi; Emma Dysmala S. (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The background of this research is that there are differences in assessing insurance funds as joint property or as separate ownership rights by the beneficiary listed in the policy. The purpose of this study was to analyze the procedure for determining the receipt of life insurance benefits. The research method chosen was using empirical juridical research methods and descriptive analytical research approaches, by analyzing the judge's decision on the application for dispute resolution regarding Sharia Insurance, Islamic Inheritance Law, in a religious court. The results of this study indicate that; the procedure for determining the receipt of life insurance benefits, namely the insured can provide life insurance for a third party or for himself, so in life insurance there are the insurer, the insured and a third party, namely the person who receives the benefit (beneficiary) from the insured in the form of the rights and obligations of each - each of these parties.